Quality of Life for Disabled Children: Parenting Patterns, Community Social Attitudes, and Social Service Role - Arini, Yusti; Sulistyarini, Ika (Sawwa: Jurnal Studi Gender, 2023)
Phenomena about children with disabilities in Salatiga still show that there are some problems related to the quality aspect of their lives. This study aims to examine parenting patterns, social attitudes, and role of the Social Service in improving the quality of life for children with disabilities. This research is a mixed-methods research using congruent design. The research subjects consisted of 66 parents of children with disabilities selected using the purposive sampling technique and 87 residents of Salatiga City selected using cluster sampling technique. Data was collected through interviews, surveys, and documentation, then analyzed quantitatively and qualitatively. The results show that parents with disabled children have a democratic parenting style, the social attitude of Salatiga City residents is good, full of empathy, and full of support; however, the Social Service Office does not yet have programs directly intended for children with disabilities in Salatiga. Research novelty is reflected by the variables and research method, which are different from previous studies.